A divisão entre trabalho, família e organizações para casais de dupla jornada: um estudo sobre homens e mulheres que vivenciam a cultura do alto desemprenho - Fernandes, Diana Rebello Neves (2017)
This thesis aims to analyze the consequences of the culture of high performance in companies on the family and personal life of men and women married and with small children (up to 12 years old), inserted in the reality of two-job couples, that is, in which both partners work in the corporate market. In order to develop this study, the theoretical framework was the culture of high performance and its consequences for the lives of workers, the insertion of women in the labor market, as the division of labor of men and women within in addition to the outsourcing of personal life. For the accomplishment of the research we opted for the use of the qualitative approach, with the use of narrative interviews and narrative analysis as method of analysis. The results suggest that the interviewed professionals continue to undergo a very intense work pace, with a longer working day for 12 or more hours a day, which has a direct impact on the time that these fathers and mothers have available to their children. So that they can stay away from home for such a long time these parents rely on the help of nannies, housekeepers or the family in the daily care with the children, resulting in the outsourcing of life. Based on the research developed, it is concluded that the employees do not seem to realize the importance of the participation of the companies in the life of the parents - through, for example, the implantation of specific policies directed to these parents. Finally, the thesis results in a new understanding of the concepts of motherhood and parenthood that raise a discussion still little explored in academia about the changes brought about by the arrival of children in the view of men, and not only of women.